Genetic insights from a Brazilian cohort of aortopathies through targeted next-generation sequencing and FBN1 direct sequencing - Juliana Rocha Ferreira; Julia Passarelli Pereira; Anna Paula Arpini Botelho; Daniele do Nascimento Aprijo; Marcelo Machado Melo; Helena Cramer Veiga Rey; Glauber Monteiro Dias (Scientific Reports)
Abstract Thoracic aortic diseases (or aortopathies) result from complex interactions between genetic and hemodynamic factors. Often clinically silent, these diseases can lead to lethal complications such as aortic dissection or rupture. This study focused on a Brazilian cohort of 79 individuals with thoracic aortic diseases and explored genetic factors through targeted next-generation sequencing (tNGS) of 15 priority genes and FBN1 direct sequencing. The majority of individuals had nonsyndromic aortopathy, with eight diagnosed with Marfan syndrome (MFS). Pathogenic or likely pathogenic variants (PV/LPV) were found in five genes, namely, FBN1, ACTA2, TGFBR2, MYLK, and SMAD3. Notably, novel variants in FBN1 were identified that contributed to Marfan-like phenotypes. The diagnostic yield for isolated aortopathies was 7.1%, which increased to 55.5% for syndromic cases. Variants of uncertain significance (VUS) were identified, emphasizing the need for further research and familial investigations to refine variant classifications. This study provides valuable insights into the genetic landscape of aortopathies in Brazil, aiding early diagnosis and personalized management.